The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1164/rccm.202104-0845oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Air Pollution Exposure and COVID-19 Mortality: A Patient-Level Analysis from New York City

Abstract: Rationale: Risk factors for COVID-19 mortality may include environmental exposures, such as air pollution.Objectives: Determine whether, amongst adults hospitalized with PCR-confirmed COVID-19, long-term air pollution exposure is associated with risk for mortality, intensive care unit (ICU) admission or intubation. Methods:We performed a retrospective analysis of SARS-CoV-2 PCR positive patients admitted to seven New York City hospitals from March 8, 2020 to August 30, 2020. The primary outcome was mortality; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 45 publications
(40 reference statements)
3
40
0
1
Order By: Relevance
“…Previous ecological studies found positive associations between long-term exposure to PM 2.5 , NO 2 and O 3 , and COVID-19 mortality and case fatality rate. 29 , 38 , 39 In other, more limited, cohort studies, Bowe and colleagues found a relative risk of 1.09 (95% CI 1.07–1.11) per 1.70 μg/m 3 increase in PM 2.5 concentration for hospital admission among American veterans who received a diagnosis of COVID-19, 16 while Bozack and colleagues 15 found relative risks of 1.23 (95% CI 1.00–1.53) for ICU admission and 1.20 (95% CI 1.03–1.39) for death, but no association with NO 2 among people admitted to hospital with COVID-19. Using slightly different methods, a cohort study in Spain and a cohort study in the Mexico City metropolitan area also found a positive association between PM 2.5 and COVID-19 severity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous ecological studies found positive associations between long-term exposure to PM 2.5 , NO 2 and O 3 , and COVID-19 mortality and case fatality rate. 29 , 38 , 39 In other, more limited, cohort studies, Bowe and colleagues found a relative risk of 1.09 (95% CI 1.07–1.11) per 1.70 μg/m 3 increase in PM 2.5 concentration for hospital admission among American veterans who received a diagnosis of COVID-19, 16 while Bozack and colleagues 15 found relative risks of 1.23 (95% CI 1.00–1.53) for ICU admission and 1.20 (95% CI 1.03–1.39) for death, but no association with NO 2 among people admitted to hospital with COVID-19. Using slightly different methods, a cohort study in Spain and a cohort study in the Mexico City metropolitan area also found a positive association between PM 2.5 and COVID-19 severity.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, a cohort study with data on individuals with SARS-CoV-2 is a more appropriate design. 6 , 14 Studies that have used individual data were conducted in specific subpopulations 15 , 16 or populations with few severe cases, 17 or had limited data on individual exposure to air pollutants. 18 In Canada, 1 ecological study found a positive association between long-term exposure to PM 2.5 and COVID-19 incidence, 19 but no published study has explored the association between air pollution and COVID-19 severity.…”
mentioning
confidence: 99%
“…In addition, some individual-level studies used spatially inaccurate or area-level estimates of long-term air pollution exposure ( Bowe et al, 2021 ; López-Feldman et al, 2021 ; Marquès et al, 2022 ; Mendy et al, 2021 ; Travaglio et al, 2021 ), which may have resulted in exposure misclassification. Furthermore, some individual-level studies included only hospitalised patients in retrospective study designs ( Bozack et al, 2022 ; Marquès et al, 2022 ; Mendy et al, 2021 ), which limits causal interpretation and generalisability.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main consequences of the changes in air quality is to be sought on the health of populations. Although epidemiological studies have highlighted the relationship between mortality records or hospital admissions and changes in air quality during COVID-19 restrictions ( Bozack et al, 2021 ; Hameed et al, 2021 ; Naqvi et al, 2021 ), little work has been done on the health impacts resulting from these changes in air pollutant levels compared to the number of studies on air quality during lockdowns. Table 1 summarizes the result of the comprehensive literature review on health risks related to changes in air pollution during lockdowns.…”
Section: Introductionmentioning
confidence: 99%